Foundation of Kardemir iron and steel factories,its contribution to Turkish economy and its privatization - Arslan, Mehmet Ziya (My University, 1999)
Kardemir is one of the biggest integrated factory in Turkiye. There had been many debates took place about its privatization in the past. In this dissertation historical bacground of Kardemir is reviewed together with its contribution to Turkish economy. It is the only example of a type of privatization that the owners are its workers. A questionnaire was prepared in order to find out what is the opinion of people who lives around Karabük about the privatization of Kardemir. The questionnaire was asked fifty persons from different educational background and occupation.The research revealed that majority of people around Karabük believes Kardemir should be privatized. This research showed that Kardemir was a loosing company before privatization due to excessive employment, inefficient managemant and lack of modernization. According to the research, the problem of excessive employment and lack of modernization on the threshold of solution whereas inefficient management seems to be present problem.
Keywords: Genel yönetim; Organizasyon ve finansman; Reorganizasyon; Şirketler_Reorganizasyon